Does Mental Health Literacy Predict Help-Seeking Behaviors Among Depressed Asian International Students? - Kim, Da Hwin; McWhorter, Emma; Castillo, Linda (Journal of International Students, 2023)
This study aimed to examine whether Asian international students’ mental health literacy predicts mental health help-seeking behaviors above and beyond known influencing factors. Hierarchical logistic regression was conducted in analyzing a national sample of 460 Asian international students who reported depressive symptomatology. Results indicated that students who identified as female and experienced more days of academic impairment were more likely to seek counseling. Additionally, having more knowledge on mental disorders and treatments and campus mental health services were positively related to help-seeking behavior. However, the ability to recognize the development of mental disorders in others was negatively associated with seeking mental health help. Implications for administrators, college program planners, and mental health providers are discussed.